Penyelesaian Sengketa Pencemaran Laut Timor Akibat Kebocoran Sumur Minyak Montara Australia Antara Indonesia dan Australia - Ambarwati, Maya Dwi (The Digest: Journal of Jurisprudence and Legisprudence, 2021)
This paper analyze the resolution of the Montara oil spill dispute between Indonesia and Australia. Analyze the responsibility of the Australian state for Timor Sea pollution due to the Montara oil leak. The analysis uses normative legal research using a statutory approach (statue approach), a conceptual approach, and a case approach. Whereas the settlement of the Montara oil spill dispute between Indonesia and Australia used a negotiation method whereby the Indonesian state filed a claim against Australia and demanded compensation for the effects of the oil spill, but Australia rejected the negotiations and the negotiations were unsuccessful. The form of responsibility of the Australian state is absolute, but in reality, if the responsibility seen or carried out is not in accordance with UNCLOS III 1982 because the Australian state is a drilling country carried out then giving permission to Thai companies in the ZEE region of the country.